ARTutor-An Augmented Reality Platform for Interactive Distance Learning - Chris Lytridis; Avgoustos Tsinakos; Ioannis Kazanidis (MDPI AG, 2018)
Augmented Reality (AR) has been used in various contexts in recent years in order to enhance user experiences in mobile and wearable devices. Various studies have shown the utility of AR, especially in the field of education, where it has been observed that learning results are improved. However, such applications require specialized teams of software developers to create and maintain them. In an attempt to solve this problem and enable educators to easily create AR content for existing textbooks, the ARTutor platform was developed. It consists of a web-based application that acts as an AR authoring tool, and an accompanying mobile application that is used to access and interact with the educational AR content. In addition, the ARTutor application allows students to ask questions verbally and receive answers based on the contents of the book. This means that the system is suitable for distance learning and promotes self-study and independent learning.